Nanocomposites based on cassava starch and chitosan-modified clay: Physico mechanical properties and biodegradability in simulated compost soil - Gustavo F. Perotti (2018)
© 2017 Sociedade Brasileira de Química. Organic-inorganic nanocomposites based on cassava starch, glycerol and chitosan-modified Veegum® HS clay mineral at two different low polymer-To-clay ratios (2.5 and 5.0 wt.%) were prepared by extrusion producing flexible, transparent and homogeneous plastics as potential candidates for agricultural purposes. X-ray diffraction and transmission electron microscopy images revealed the presence of both intercalated and exfoliated nanocomposites in all samples, in which exfoliation is the predominant type of microscopic structure. Statistically significant improvements of over 20% on the tensile strength and Young's modulus were observed for samples containing chitosan-modified clay in comparison to pristine thermoplastic starch. Chitosan deeply affects the conversion of polymer carbon to CO2 through biodegradation. Mineralization values for the sample loaded with 5.0 wt.% of chitosan-modified clay in simulated compost soil showed a reduction of almost 40% in comparison to thermoplastic starch, benefiting applications where delay degradation is required.